NANODIAMOND SYNTHESIS AND CHARACTERIZATION, AS WELL AS ITS USE AS AN ANTI-POLISHING AGENT ON SIO2 SUBSTRATE - Durlab Das, S.Venkatesan, KARTHIK A, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Nanodiamond particles were produced, purified, and described in the current work. The surface of the nanodiamond was then oxidised to create a uniform coating of COOH groups. Finally, the functionalized particles were placed on the SiO2 substrate and their anti-polishing properties were studied. FT-TR, TGA, TEM, and SEM were used to characterise the products of this study